Framework for orientation of Striga research at IITA - Cardwell, K.F.; Smith, J.; Weber, G.; Awad, A. (1991)
Striga research at IITA is conducted by multidisciplinary team. To coordinate and focus the activities of the team, two models have been developed that attempt to provide a framework for research. One model addresses the agro biological aspects of Striga seed population dynamics. This model shows the combination of, and the necessary impact of, each of various technological inputs to stop or decrease Striga seed population growth. The second model has been adapted to assess the likelihood of adoption of control packages based on socio economic criteria. This model analyses the cost of using different technologies to control Striga based on resource endowments in different socio economic environments, which in turn provides guidelines as to which technologies are likely to be acceptable in those environments. A matrix of Striga infestation level by socio economic environment has been developed to integrate the models, to select biologically effective and economically viable Striga management schemes